Effect of Jala Neti and Soopya Yoosha in Allergic Rhinitis (International Journal of Ayurveda and Pharma Research, 2024)
Allergic rhinitis is a common health problem affecting immune system. It is an allergic response to specific allergens causing the inflammation of nasal mucosa. Allergic rhinitis is a major risk factor for poor asthma control and affects quality of life. Cardinal symptoms include nasal congestion, rhinorrhea, and pruritis of the nose and eyes. Patients who suffer from allergic rhinitis sustain significant morbidity and loss of productivity. The symptoms of allergic rhinitis can be co-related with Lakshanas of Pratishyaya mentioned in Ayurveda. This study aimed at yoga therapy and diet as an efficient treatment protocol for the disease. Jalaneti procedure which was mentioned in yoga, helped in preventing and managing upper respiratory tract infections. Since ancient time Yoosha had been suggested as Pathya for both healthy and diseased people. Soopya yoosha containing Mudga and Moolaka is a dietary preparation having Pratishyayahara property. In present study Jalaneti and Soopya yoosha were used in patients of allergic rhinitis.